Effect of Brand Communication and Experience on Loyalty: Mediating Effect of Brand Satisfaction and Trust. (Case Study of Customers of Inul Vista Karaoke, Semarang, Central Java, Indonesia) - Ngatno, ngatno ngatno (Archives of Business Research, 2017)
This study examined the influence of brand communication and experience on brand satisfaction, trust and loyalty. The sample of this study was customer of “Inul Vista Karaoke” in Semarang, Central Java, Indonesia. 220 questionnaires were distributed with 95,91% response rate. The data were analyzed using Partial Least Square (PLS). The results reveal that: a) brand communication and experience have a positive effect on brand satisfaction and trust. b) Brand communication is not direct effect on brand loyalty but brand experience is. c). Brand satisfaction and trust shows partially mediates beetwen brand experience and loyalty, and fully mediates beetwen brand communication and loyalty. The findings offer insight for Inul Vista Karaoke to increase loyalty must to be more increase brand experience than brand communication.